PENGARUH PENINGKATAN TEKANAN TERHADAP UNJUK KERJA ENGINE SATU SILINDER - Abrar Riza Riza (Program Studi Teknik Mesin Universitas Tarumanagara, 2018)
Ignition timing in an important at internal combustion. Timing has a role to synchronize the system in order to get optimal energy. Ignition time is directly related to working pressure in the combustion chamber. The delay combustion will result in higher work pressure. Increased work pressure can increase the performance of the fuel motor and can reduce emissions because combustion is encouraged to be more perfect. Various methods can be done to accompany the conditions of delay combustion to increase work pressure by increasing the octane number. This research focuses on the influence of the one-step gasoline engine performance variable. Effective octane enhancing solutions are used to increase pressure with the concept of combustion delay. Octane-enhancing solutions can be used in various types or concentration in fuel. The results of the study are that torque can increase up to 15% and the power can increase up to 20% compared to standard testing conditions. This is effective at medium to high engine speed.